Hubungan Antara Stres Akademik Dengan Konsentrasi Belajar Siswa SMA Kelas XI di Sekolah SMA Negeri 1 Citeureup - Noor Aini Yasmin; Gunawan Ikhtiono; Noor Isna Alfaieni (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
Concentration in learning is a key factor that determines success in education. In this era, concentration has become one of the weaknesses of students. Students' concentration is very easily influenced. One of the factors that can affect concentration in learning is pressure and depression, which fall under the category of stress. The stress often experienced by students is academic stress, which occurs within the scope of academics or education. This research aims to determine whether there is a relationship between academic stress and the concentration of eleventh-grade students at SMA Negeri 1 Citeureup. This research method uses a quantitative research approach and the type of method used is the correlational method. From the correlation test conducted, a correlation value of -0.492 was obtained, which means that there is a significant negative correlation with very low correlation strength, where the very low correlation range is within 0.00-0.199. It can be interpreted that the higher the academic stress experienced by students, the lower the concentration of students' learning, and conversely, the lower the academic stress experienced by students, the higher the level of students' learning concentration.